Confidential voice - the secret revealed - Serrão, Bianca Joelene (My University, 2014)
Rationale: Evidence based practice proposes an ethical method of addressing longstanding questions about clinical practice in communication disorders. The existing knowledge base available on clinical interventions is frequently incomplete, potentially incorrect and biased according to Dodd (2007). Confidential Voice Therapy technique is a technique that was introduced by Colton and Casper in 1990 and has been used to treat a myriad of voice disorders since its inception. A small number of studies have been done to evaluate this treatment’s efficacy. It has been proven effective at a physiological level and patients have perceived it to be beneficial. However the founders themselves have stated that this technique it is not effective for all patients it was employed on. However they failed to state why this is so. Aims: The current study looked at how the confidential voice technique changes the voices of patients with hyperfunctional voice disorders physiologically, acoustically and in terms of air flow, as well as patients’ perceptions of the technique and its effect on their voices. Method: A quasi-‐experimental design, single group pre-‐test post-‐test design was employed. A sample of twelve individuals with hyperfunctional voice disorders were examined using a flexible fiberoptic examination, acoustic analysis, aerodynamic measures, a self-‐constructed questionnaire and stroboscopic examination prior to employing confidential voice technique and again during the use of confidential voice technique. The results of the acoustic analysis and aerodynamic measures were analysed using paired t-‐tests while the questionnaire and SERF results were analysed descriptively. Results: The overaching result of this study was that the confidential voice technique did not have a significant effect on the voices of individuals with hyperfunctional voice disorders. There were exceptions to this, as five out of thirty-‐two parameters were significant in terms of acoustic analysis (i.e. Average Fundamental Frequency, Mean Fundamental Frequency, Average Pitch Period, Relative Average Pertubation and Smoothed Pitch Perturbation Quotient) and half of the aerodynamic measures used were significant (i.e. Maximum SPL, Maximum Pitch, Pitch Range, Phonation Time and Peak Inspiratory Airflow). Stroboscopic evaluations revealed changes in glottal closure, mucosal wave and amplitude, supraglottic activity and phase closure. In terms of the participants perceptions, the majority were able to identify the need for the technique however felt that it required a significant amount of concentration and limited them in their daily lives. Conclusions: Despite the lack of statistical significance the results of this study have provided information that should inform practice and result in more successful treatment of patients as the clinician should now be able to estimate the potential effectiveness of the technique for a specific patient with a hyperfunctional voice disorder. It is envisioned that the present study provided objective information on the question of how and why confidential voice technique works in the treatment of hyperfunctional voice disorders as well how patients perceive the technique which has implications for therapeutic adherance. Keywords: Voice therapy; Hyperfunctional Voice Disorders; Confidential Voice; Evidence-‐based practice
The Discipline of Speech Pathology and Audiology School of Human and Community Development Faculty of Humanities University of the Witwatersrand In fulfillment of the requirements For the degree M.A. Speech Therapy (by Research)